Impact of worklist selection on point-of-care ultrasound workflow – a quality improvement project - Jonathan Rowland; Jessa Baker; Natassia Dunn; Matthew Whited; Soheil Saadat; J. Christian Fox (BMC Health Services Research)
Abstract Background Research demonstrates that Point-of-care ultrasound (POCUS) improves clinical outcomes for patients. Improving clinician satisfaction with POCUS should promote utilization into everyday practice, leading to improved clinical outcomes. Despite this benefit, there are still barriers to use including POCUS workflow. This project was undertaken to improve the functionality of the existing POCUS workflow and move toward an “encounter-based” system by automating worklist generation. It aimed to streamline the POCUS workflow, primarily determine if there was improved clinician satisfaction with the new workflow, and secondarily determine the change in revenue generation from decreased errors in data entry. Methods A new workflow was created which automatically populated every registered Emergency Department (ED) patient into the worklist upon patient registration. Clinician feedback on their use of the new workflow was sought via survey after implementation. The number of medical record number (MRN) entry errors prior to and following implementation was manually reviewed and calculated. Results There was a strong preference for the new workflow, with 36 of 38 (94.7%) clinicians finding it to be more convenient and 37 of 38 (97.4%) finding it to be preferable to use compared to the old workflow. Implementation also resulted in a 36% reduction in database studies containing an MRN data entry error. Conclusions An “encounter-based” workflow is strongly preferred over manual data entry for POCUS workflow among clinicians. Additionally, there was no cost to the intervention and the total data entry errors were significantly reduced, allowing for improved quality review and increased revenue.